Media Ular Tangga Pada Materi Komponen Biotik Dan Abiotik - Shofiyatul Laily27; Lina Arifah Fitriyah (Universitas Islam Madura, 2022)
Learning media is an intermediary or message in the form of objects that can be seen and heard in order to provide effectiveness to student learning outcomes. In learning media, it is very necessary to increase efficiency during the learning process. Snakes and ladders media is an option because its use in learning can increase student activity. The purpose of research on this learning media is expected to describe the sequence of the development process in the snake ladder media material for abiotic biotic components, and can determine the validity of the development of snake ladder media. The type of research used is a development model that refers to the ADDIE research design, namely the stage (Analyze, design, development, implementation, evaluation). This research produces data in the form of a snake and ladder media development process using the ADDIE model, namely the Analyze stage, namely analyzing the material and students. Design which refers to the design of learning indicators and media to be developed. Development, namely the process of making snake and ladder media which was designed at the previous design stage. Then, the implementation stage cannot be carried out systematically, because it only reaches the validity test. Finally, evaluation, which is the final stage of snake and ladder media on biotic and abiotic component materials. In the media validation process, it is carried out by material expert validators, media experts and teachers. Then the results of the validation obtained a score of 94.6% from media experts, 82.1% by material experts, and 94.6% from science teachers. With these results, the snake and ladder media analyzed for its development process with the ADDIE approach model is declared